The relative effectiveness of chlorine and antibiotic treatments for stony coral tissue loss disease - Forrester, Graham E.; Arton, Laura; Horton, Argel; Aeby, Greta (Frontiers in Marine Science, 2024)
Stony coral tissue loss disease (SCTLD) causes severe mortality in many hard corals and is now present in most of the Caribbean. The application of amoxicillin paste is currently the most successful local intervention to treat SCTLD lesions in nature, but the potential development of antibiotic resistance makes alternatives valuable. In a preliminary field trial (n = 84 corals), we compared two treatments against SCTLD, (1) amoxicillin paste and (2) chlorine mixed with cocoa butter paste and covered with a clay band. We found that amoxicillin and chlorine treatments both significantly reduced the rate of tissue loss in SCLTD-affected corals as compared to controls. Amoxicillin treatment was the most effective and effectively halted tissue loss in 78% of colonies. Even so, chlorine treated colonies lost tissue at approximately half the rate of untreated controls. The non-specific antiseptic nature of chlorine treatments may also be useful for other tissue loss diseases of unknown etiologies. Although, not perfect, the chlorinated cocoa butter treatment can be added to the growing list of methods to reduce mortality from disease in the field.